Pengaruh Beban Kerja dan Pemberian Insentif terhadap Kinerja Karyawan UlaMM dengan Kepuasan Kerja sebagai Variabel Intervening pada PT Permodalan Nasional Madani Cabang Kabanjahe - Indra Irawan; Siti Safaria (Sekolah Pascasarjana Perbanas Jakarta, 2023)
This study aims to analyze the effect of workload on employee performance, the effect of giving incentives on employee performance, the effect of workload on job satisfaction, the effect of giving incentives on job satisfaction, the effect of satisfaction on employee performance, the effect of workload on employee performance through job satisfaction, the influence giving incentives to employee performance through job satisfaction at PT. PNM Kabanjahe Branch, using a survey, random sampling with 76 respondents, the results of research workload has a significant effect on performance, incentives have a significant effect on performance, workload has a significant effect on job satisfaction, incentives have a significant effect on satisfaction has a significant effect on workload performance has a significant effect on employee performance mediated by job satisfaction, incentives have a positive and significant effect on employee performance mediated by job satisfaction. Recommendations are expected that the organization always improves and maintains employee performance.